To grab or not to grab? the role of trust and perceived value in on-demand ridesharing services - Cheng, Eugene Xi Aw; Kamal Basha, Norazlyn; Siew, Imm Ng; Sambasivan, Murali (Emerald, 2019)
Purpose The purpose of this paper is to empirically test the antecedents and outcome of perceived value and trust toward on-demand ridesharing services (ODRS). The antecedents are perceived innovativeness, perceived personalization, perceived usefulness of rating system and service personal values. The outcome is the continuance intention toward ODRS. This study also aims to uncover the mediating role of trust and the moderating role of technology readiness. Design/methodology/approach The ODRS considered in this research are Grab and Uber in the context of Malaysia. A questionnaire was constructed, and responses were obtained from 280 Malaysian consumers who have experienced ODRS. The authors tested the framework using partial least square structural equation modeling technique. Findings The result indicates several significant relationships: perceived personalization, perceived usefulness of rating system and service personal values significantly influence perceived value and trust; trust mediates the relationships between perceived personalization, perceived usefulness of rating system, service personal values and perceived value; perceived value significantly influences continuance intention; and technology readiness moderates the relationship between perceived personalization and perceived value. Originality/value The current study adds significantly to the body of knowledge about ODRS by examining the direct determinants of trust and perceived value, and exhibiting how trust mediates the mechanism. This study also illustrates the interplay of moderator (technology readiness) and perceived value.